Influenza-like illness is associated with high pneumococcal carriage density in Malawian children. Issue 4 (October 2020) - Nyazika, Tinashe K.; Law, Alice; Swarthout, Todd D.; Sibale, Lusako; ter Braake, Danielle; French, Neil; Heyderman, Robert S.; Everett, Dean; Kadioglu, Aras; Jambo, Kondwani C.; Neill, Daniel R.
Highlights: Influenza-like illness (ILI) in children is associated with high pneumococcal carriage density. Children with ILI harboured more viral organisms than asymptomatic healthy children. Children with ILI patients had higher IL-8 levels in nasal aspirates than asymptomatic healthy children. Summary: Background: High pneumococcal carriage density is a risk factor for invasive pneumococcal disease (IPD) and transmission, but factors that increase pneumococcal carriage density are still unclear. Methods: We undertook a cross-sectional study to evaluate the microbial composition, cytokine levels and pneumococcal carriage densities in samples from children presenting with an influenza-like illness (ILI) and asymptomatic healthy controls (HC). Results: The proportion of children harbouring viral organisms (Relative risk (RR) 1.4, p = 0.0222) or ≥ 4 microbes at a time (RR 1.9, p < 0.0001), was higher in ILI patients than HC. ILI patients had higher IL-8 levels in nasal aspirates than HC (median [IQR], 265.7 [0 – 452.3] vs. 0 [0 – 127.3] pg/ml; p = 0.0154). Having an ILI was associated with higher pneumococcal carriage densities compared to HC (RR 4.2, p < 0.0001). Conclusion: These findings suggest that children with an ILI have an increased propensity for high pneumococcal carriage density. This could in part contribute to increased susceptibility to IPD and transmission in the community.